2021
DOI: 10.1111/acel.13525
|View full text |Cite
|
Sign up to set email alerts
|

Senescence‐induced changes in CD4 T cell differentiation can be alleviated by treatment with senolytics

Abstract: Aging and senescence impact CD4 T helper cell (Th) subset differentiation during influenza infection. In the lungs of infected aged mice, there were significantly greater percentages of Th cells expressing the transcription factor FoxP3, indicative of regulatory CD4 T cells (Treg), when compared to young. TGF‐beta levels, which drive FoxP3 expression, were also higher in the bronchoalveolar lavage of aged mice and blocking TGF‐beta reduced the percentage of FoxP3+ Th in aged lungs during influenza infection. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 53 publications
2
26
2
Order By: Relevance
“…Enhanced populations of these cells could possibly lead to induction of IL-17-producing cells and then to the recruitment of neutrophils to the lung-a hallmark of COVID-19 (Blanco-Melo et al, 2020). These data are in agreement with recent findings implicating elevated levels of TGF-b from senescent cells, which we also find to be increased in number in aged animals (Lorenzo et al, 2022). This biology would explain why we see a significant increase of neutrophils in the respiratory tract of older individuals, as TGF-b signaling induces IL-17, which in turn mediates neutrophil recruitment.…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced populations of these cells could possibly lead to induction of IL-17-producing cells and then to the recruitment of neutrophils to the lung-a hallmark of COVID-19 (Blanco-Melo et al, 2020). These data are in agreement with recent findings implicating elevated levels of TGF-b from senescent cells, which we also find to be increased in number in aged animals (Lorenzo et al, 2022). This biology would explain why we see a significant increase of neutrophils in the respiratory tract of older individuals, as TGF-b signaling induces IL-17, which in turn mediates neutrophil recruitment.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, studies from our lab and others have begun to apply senolytic strategies to overcome age-related deficits during an infection. Our work with flu infection demonstrated that treatment of aged mice with D+Q decreased the proportion of Tregs in the lungs during infection in favor of a more healing GATA-3 expressing Th2 T cell population by mitigating the senescent environment ( 145 ). Strikingly, D+Q treatment completely abrogated TGF-β production in the lung following infection.…”
Section: Role Of Senolytics In Potentiating Aged Immune Responsesmentioning
confidence: 94%
“…On the other hand, the so-called “anti-aging drugs”, senolytics, promote removal of senescent immune cells that accumulate with age [ 170 ]. Specifically, in old mice, it has been demonstrated that senolytic drugs can impact CD4 + T cells, most likely by modulating the microenvironment, which can then positively influence T cell differentiation during the response to influenza infection [ 171 ].…”
Section: Strategies To Reverse Immunosenescence Of Adaptive Immunity ...mentioning
confidence: 99%